Identification and Validation of Th1-Selective Epitopes Derived from Proteins Overexpressed in Breast Cancer Stem Cells - Denise L. Cecil; Daniel Herendeen; Meredith Slota; Megan M. O’Meara; Yushe Dang; Lauren Corulli; Mary L. Disis (Vaccines)
Background: Breast cancer stem cells (CSCs), particularly those enriched in triple-negative breast cancer (TNBC), are key contributors to tumor recurrence, metastasis, and resistance to therapy. CSCs often undergo epithelial-to-mesenchymal transformation (EMT), enhancing their invasiveness. Immune-based strategies that selectively target CSC/EMT antigens offer a promising therapeutic approach. Methods: Twelve candidate CSC/EMT-associated proteins were identified through a systematic literature review. Human serum samples were assessed for antigen-specific IgG using ELISA. Th1/Th2 cytokine profiles, in response to predicted MHC II epitopes, were measured by ELISPOT in PBMCs. Epitope immunogenicity and tumor inhibition were evaluated in murine models, using either TNBC or luminal B syngeneic breast cancer cell lines. Results: Six of the candidate proteins (SOX2, YB1, FOXQ1, MDM2, CDH3, CD105) elicited antigen-specific IgG in human serum. Th1-selective epitopes, defined by high Th1/Th2 ratios, were identified for five of these proteins. Immunization of mice with peptide pools derived from CD105, CDH3, MDM2, SOX2, and YB1 induced significant antigen-specific IFN-γ responses. Tumor growth was significantly inhibited in the vaccinated mice across both the TNBC and luminal B breast cancer models, with mean tumor volume reductions ranging from 61% to 70%. Conclusions: CSC/EMT-associated antigens are immunogenic in humans and can be targeted using Th1-selective epitope-based vaccines. Immunization with these epitopes effectively inhibits tumor growth in multiple murine models of breast cancer. These findings support further clinical evaluation of CSC/EMT-targeted vaccines, especially for high-risk or advanced-stage breast cancer patients.